2005
DOI: 10.1359/jbmr.050801
|View full text |Cite
|
Sign up to set email alerts
|

A New Selective Estrogen Receptor Modulator, CHF 4227.01, Preserves Bone Mass and Microarchitecture in Ovariectomized Rats

Abstract: A new SERM, CHF 4227.01, given to 6-month-old female rats immediately after ovariectomy, preserved bone mass and bone microarchitecture without affecting uterus weight. It also decreased serum cholesterol and fat mass in estrogen-deficient rats. Introduction:We tested the effect of a new benzopyran derivative, CHF 4227.01, with selective estrogen receptor modulator (SERM) activity on bone mass and biomechanics in ovariectomized (OVX) female rats in comparison with 17␣-ethinylestradiol (EST), raloxifene (RLX), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
13
0
2
Order By: Relevance
“…Specimens were randomized and tested in a three‐point bend configuration in accordance with ASTM D790 (ASTM International, West Conshohocken, PA, USA) using a typical, commercially available three‐point bend fixture, which was mounted to a MTS Systems' Synergie 200 (MTS, Eden Prairie, MN, USA) electromechanical materials testing load frame. In order to introduce tension on the anterior aspect, femurs were positioned condyles up and to the right on the 15,110 mm support span (Armamento‐Villareal et al 2005). Loading was applied to the posterior aspect of the mid‐diaphysis of each femur via the loading actuator at a displacement‐control rate of 0.1 mm/s (6 mm/min).…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were randomized and tested in a three‐point bend configuration in accordance with ASTM D790 (ASTM International, West Conshohocken, PA, USA) using a typical, commercially available three‐point bend fixture, which was mounted to a MTS Systems' Synergie 200 (MTS, Eden Prairie, MN, USA) electromechanical materials testing load frame. In order to introduce tension on the anterior aspect, femurs were positioned condyles up and to the right on the 15,110 mm support span (Armamento‐Villareal et al 2005). Loading was applied to the posterior aspect of the mid‐diaphysis of each femur via the loading actuator at a displacement‐control rate of 0.1 mm/s (6 mm/min).…”
Section: Methodsmentioning
confidence: 99%
“…Right and left femurs were excised and cleaned of muscle and connective tissue. Micro‐CT scans were taken of each bone sample (μCT 40, Scanco Medical AG, Basserdorf, Switzerland), using a modification of a previously described procedure 26 . Bones were stabilized in 1.5% agarose gel and 16 μm voxel resolution images of the distal femoral epiphysis and midshaft of the femoral diaphysis were scanned.…”
Section: Methodsmentioning
confidence: 99%
“…Micro-CT scans were taken of each bone sample (CT 40, Scanco Medical AG, Basserdorf, Switzerland), using a modification of a previously described procedure. 26 Bones were stabilized in 1.5% agarose gel and 16 m voxel resolution images of the distal femoral epiphysis and midshaft of the femoral diaphysis were scanned. Specifically, a 1 mm thick middiaphyseal region and a 0.5 mm thick section encompassing the distal femoral epiphysis were analyzed.…”
Section: Bone Microstructurementioning
confidence: 99%
“…CHF4227 significantly prevents the development of DMBA-induced mammary tumors in rats [184]. It preserves bone mass without affecting uterine weight and decreases serum cholesterol and fat mass in ovariectomized rats [185]. A recent phase I study showed CHF4227 is well-tolerated, as 28 days of treatment has a positive effect on the serum lipid profile and bone markers without any negative effects on the endometrium or the fibrinolytic system.…”
Section: New Sermsmentioning
confidence: 99%